Model Strategi Prospektif Kinerja Manajemen di Perusahaan Tour & Travel - Rudy Aryanto; Yuniarty Yuniarty (Binus Business Review, 2010)
This study aimed to build a prospective management model of sustainable tour packages in PT. Golden Rama Express. Given the complexity and the many interrelated factors in the performance management packagetours, it is necessary to approach a holistic system. First, the method used in developing the performance management model is a sustainable package tour and, second, using prospective analysis. Determination of the attributes that reflect the sustainability performance of the tour package is based on field studies. Based on the four dimensions of sustainability, namely the dimensions before the trip, during trip, etc., and the tour leader aredetermined as much as 23 attributes. Attributes in four dimensions for each package tour Junglelicious Africa, Asia Splendid, Adventurous Australia and New Zealand, Europe Romantical and Marvelous the U.S. and Canada. After obtained the level of sustainability index values of each dimension that can be categorized into the not sustainable until very sustainable values of the index, combination of these factors forms the basis of development models.. Based on the scenario that was built and in order to achieve the ideal scenario is the recommended scenario is the optimistic scenario.